2007
DOI: 10.1177/0020872807076048
|View full text |Cite
|
Sign up to set email alerts
|

Learning the lessons of Bam

Abstract: English A massive earthquake devastated the city of Bam in Iran in 2003. The survivors became rapidly disenfranchised from the relief efforts and social capital diminished significantly. This article details the breakdown in social capital and links are made between the sustainment of social capital and the social work role. French En 2003, un tremblement de terre de grande magnitude a dé vasté la ville de Bam en Iran. Les survivants ont vite é té mis à l'é cart des efforts de relè ve et le capital social a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Yet, this research shows that, during the longer-term recovery phase, social capital can be undermined and eroded by the response interventions. Such an outcome has been pinpointed in other studies (see, for example, Aghabakhshi and Gregor, 2007).…”
Section: Conceptualising Complex Socio-ecological Systems As a Panarcsupporting
confidence: 57%
“…Yet, this research shows that, during the longer-term recovery phase, social capital can be undermined and eroded by the response interventions. Such an outcome has been pinpointed in other studies (see, for example, Aghabakhshi and Gregor, 2007).…”
Section: Conceptualising Complex Socio-ecological Systems As a Panarcsupporting
confidence: 57%
“…35 In addition, social capital contributes to the reconstruction of the community. 36 Therefore, enhancing social capital in the evacuees’ community could improve their health. In fact, it was reported that interventions to facilitate social participation in local events by evacuees in prefabricated housing improved their health.…”
Section: Discussionmentioning
confidence: 99%
“…Yanay and Benjamin (2005) reached similar conclusions in their study of the role of social workers in disaster. Aghabakhshi and Gregor (2007) believe that the survivors of a disaster are not helpless people. Using their energy instead of compassion and mourning can reduce their anger and increase their empowerment and participation (Aghabakhshi and Gregor, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Aghabakhshi and Gregor (2007) believe that the survivors of a disaster are not helpless people. Using their energy instead of compassion and mourning can reduce their anger and increase their empowerment and participation (Aghabakhshi and Gregor, 2007). Social workers have a key role in responding to natural disasters.…”
Section: Discussionmentioning
confidence: 99%